Мезолітична стоянка Ласпі 7 на південному березі Криму, Україна - Телегін, Д.Я.; Залізняк, Л.Л.; Яневич, О.О. (Археологія і давня історія України, 2020)
Стаття присвячена підсумкам багаторічних досліджень під проводом Д. Я. Телегіна однієї з ключових мезолітичних пам’яток Кримського півострова — стоянки Ласпі 7 на Південному березі Криму. Late Mesolithic Laspi 7 site is situated in Ukraine, in the West part of the South Coast of Crimea, in the Laspi Bay, Black Sea coast (44°24’48.5”N 33°42’41.3”E). It was investigated under the direction of prof. Dmytro Telegin in the second half of 1970s. The site was destroyed by Russian occupation power. There were 7 cultural layers of the site, which had the thickness near 2 m. There was Kokkenmedding — clay sediment with crushed stone and with unusual great number of the Helix albescens shells, ash and charcoal. Any structures of the cultural layer are not traced. Archaeological materials of Laspi 7 are represented by numerous flint collection (2347 eks.), bone tools assemblage (13 eks.), ocher, faunistic materials etc. Flint complexes from all cultural layers generally are similar. Most of the cores are pyramidal. Prismatic and pencilshaped cores are single. Microlithic assemblage consists of geomethric miсroliths (asymmetrical and symmetrical trapezoids); single backed microliths and truncated blades. Scrapers are mostly semicircular on the flakes, single end scrapers are on the blades. Most of the burins are on the flakes, they are angle and, in smaller quantities, lateral. There are some «Kukrek type» burins with numerous worked parts. Angle burins on the blades are not numerous. Unusual big quantity of encoches is amazing. There is one Kukrek insert. Bone tools are very different (13 eks.): base part of the harpoon, fragment of the point with the grooves, different points, the borers, partly worked boar tusks, fragment of the antler socket. The age of Laspi 7 is 8600—7000 В Р. The most true 14C dates are 8625 ± 40 BP (GrA-35704) and 8620 ± 40 BP (GrA-35703). Laspi 7 flint assemblage is typical for the Late Mesolithic Murzak-Koba culture of Mountain Crimea. Laspi 7 is a shining example of the «revolution of the wide range» in Crimea. Inhabitants of the site used very different food resources: ungulates (red deer, boar, roe deer), birds (above all bustard), fish (catfish and pike perch), Helix albescens snails. Numerous ornito-, ihtio- and malakofauna dates evidences about the occupation of the site in autumn, winter, and spring time. Probably, the site was visited periodically during these seasons.